Research on the influence of tire parameters on coupled brakeinduced vibration of telescopic landing gear with two wheels - FENG Guang; YIN Qiaozhi; YANG Le; ZHANG Songyang; SONG Jiayi (Hangkong gongcheng jinzhan, 2023)
Currently,the research on the low-frequency brake coupling vibration of aircraft landing gear mainly focuses on the analysis of the longitudinal single degree of freedom vibration characteristics of landing gear considering the influence of tire parameters,but the research on the multi-degree-of-freedom low-frequency brake coupling vibration characteristic is relatively lacking. A taxiing and braking analysis model for rigid-flexible coupling of two-wheel strut landing gear is established in the Simcenter 3D dynamics analysis software. The effect of wheel vertical stiffness and cornering stiffness on multi-freedom coupling vibration of telescopic landing gear with two wheels is studied. The results show that the vertical stiffness of the tire is of a great influence on the vibration of the landing gear in the lateral and torsional direction. The vertical stiffness of the tire changes by 33% and the vibration in the lateral and torsional direction changes by about 5%. The cornering stiffness of the tire is of a great influence on the vibration of the landing gear in the lateral. The cornering stiffness of the tire changes by 33% and the vibration in the lateral direction changes by about 15%.